Diamine, its production method and polymer
Patent Information
- Application Number
- JP2023151776
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-09-14
- Filing Date
- 2023-09-19
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2039-09-12
Smart Images

Figure 0007633608000001 
Figure 0007633608000002 
Figure 0007633608000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel liquid crystal aligning agent and a liquid crystal alignment film, as well as a liquid crystal display element, a novel diamine, a production method thereof, and a polymer thereof. [Background technology]
[0002] Currently, liquid crystal display elements are widely used as display parts for personal computers, mobile phones, television receivers, etc. A liquid crystal display element includes, for example, a liquid crystal layer sandwiched between an element substrate and a color filter substrate, pixel electrodes and a common electrode for applying an electric field to the liquid crystal layer, a liquid crystal alignment film for controlling the alignment of liquid crystal molecules in the liquid crystal layer, and a thin film transistor (TFT) for switching an electric signal supplied to the pixel electrode. Of these, the liquid crystal alignment film is produced by applying a polyimide-based liquid crystal alignment agent made of a solution of polyimide, which is a polyimide precursor (also called "polyamic acid"), or its imidized product, to a substrate to form a film.
[0003] In recent years, liquid crystal display elements have become more powerful, larger in area, and more energy-efficient, and in addition, they are now used in a variety of environments, so the properties required of liquid crystal alignment films are becoming more stringent. Therefore, various methods such as changing the structure of polyamic acid or polyimide, blending polyamic acid or polyimide with different properties, or adding additives have been used to improve liquid crystal alignment and electrical properties, as well as to control the pretilt angle.
[0004] As an example of a method for improving the properties of a liquid crystal alignment film, the application of a diamine having a novel structure, which is a raw material for polyamic acid, has been proposed. For example, Patent Document 1 discloses a liquid crystal alignment agent containing a diamine having a novel structure and an aliphatic tetracarboxylic acid derivative, and by using this liquid crystal alignment agent, it is possible to provide a liquid crystal display element that is excellent in voltage retention and can reduce charge accumulation.
[0005] However, as liquid crystal display elements become more sophisticated, the characteristics required for liquid crystal alignment films are becoming more stringent, and it is difficult to satisfy all the required characteristics using conventional techniques alone.
[0006] On the other hand, a common method for aligning liquid crystals is a rubbing method in which a polymer film such as polyimide is applied to a substrate such as glass, and the surface is rubbed in a predetermined direction with fibers such as nylon or polyester. However, this rubbing method generates fine dust and static electricity discharge due to friction between the fibers and the polymer film, which may cause serious problems during the manufacture of liquid crystal panels.
[0007] In order to solve the problems of the rubbing method, a photo-alignment method is known in which there is no friction in the polymer film and anisotropy is induced by light irradiation to align the liquid crystal. In the photo-alignment method, a photoreaction such as a photodecomposition reaction or a photodimerization reaction is caused in the polymer contained in the liquid crystal alignment film by irradiation with polarized ultraviolet light, thereby fixing the alignment direction of the liquid crystal. As the demand for high-definition and high-quality liquid crystal display elements increases, such a photo-alignment method is being applied to liquid crystal display elements of the IPS (In-Plane Switching) and FFS (Fringe Field Switching) types, which are horizontal electric field driving methods (see, for example, Patent Document 2). In addition, a method of combining the IPS method with the PSA method has been developed in recent years to further improve the alignment ability.
[0008] However, since polyimide used in the photo-alignment method generally has poor solubility in solvents, it is difficult to directly apply polyimide in the process of forming an alignment film by applying the polyimide in a solution state. For this reason, a precursor such as polyamic acid or polyamic acid ester, which has excellent solubility, is applied, and polyimide is formed through a heat treatment process, and then oriented by light irradiation. However, a lot of energy is required to obtain sufficient liquid crystal alignment by irradiating a polyimide film with light. Therefore, it is difficult to actually ensure productivity, and there is also a constraint that a heat treatment process is required to obtain alignment stability after light irradiation. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] International Publication No. 2010 / 053128 [Patent Document 2] JP 2013-080193 A Summary of the Invention [Problem to be solved by the invention]
[0010] In view of the above circumstances, the present invention aims to provide a liquid crystal alignment agent, a liquid crystal alignment film and a liquid crystal display element, as well as a diamine and a production method thereof, and a polymer thereof, which use a novel diamine for improving the characteristics of a liquid crystal display element. [Means for solving the problem]
[0011] An embodiment of the present invention for solving the above-mentioned problems is a liquid crystal aligning agent containing at least one polymer selected from a polyimide precursor containing a structural unit represented by the following formula [3-1] and a polyimide which is an imide compound thereof.
[0012] [ka] In the formula, V 0 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and W 1 is a divalent organic group represented by the following formula [2-1], R 3 and R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.
[0013] [ka] In the formula, Y 1 is a tetravalent organic group having an alicyclic structure, and X 1 , X 2 is a divalent organic group, Z 1 , Z 2are each independently a single bond, -NH-, or -O-; R 1 and R 2 each independently represents an alkyl group having 1 to 5 carbon atoms, and * represents a bonding site. Effect of the Invention
[0014] According to the present invention, it is possible to provide a novel liquid crystal aligning agent for improving the characteristics of a liquid crystal display element, a liquid crystal alignment film and a liquid crystal display element, as well as a novel diamine, a production method thereof, and a polymer thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will now be described in more detail.
[0016] The liquid crystal aligning agent of the present invention contains at least one polymer (hereinafter also referred to as specific polymer A) selected from a polyimide precursor containing a structural unit represented by the following formula [3-1] and a polyimide which is an imide compound thereof. More specifically, the liquid crystal aligning agent contains the specific polymer A and an organic solvent.
[0017] [ka] In the formula, V 0 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and W 1 is a divalent organic group represented by the following formula [2-1], R 3 and R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms.
[0018] [ka] In the formula, Y 1 is a tetravalent organic group having an alicyclic structure, and X 1 , X 2 is a divalent organic group, Z 1 , Z 2 are each independently a single bond, -NH-, or -O-; R1 and R 2 each independently represents an alkyl group having 1 to 5 carbon atoms, and * represents a bonding site.
[0019] The structure of the formula [2-1] above is a divalent group derived from a diamine represented by the following formula [1] (hereinafter, also referred to as the diamine of the present invention), so the diamine of the present invention will be described first. 1 , X 1 , X 2 , Z 1 , Z 2 , R 1 and R 2 The specific examples and preferred structures in the formula [3-1] are the same as those in the formula [1]. 1 As long as it is a divalent organic group represented by the formula [2-1], one type may be contained in the same polymer, or two or more types may be contained in the same polymer.
[0020] <Diamine> The diamine of the present invention is represented by the following formula [1].
[0021] [ka] In the formula, Y 1 is a tetravalent organic group having an alicyclic structure, and X 1 , X 2 is a divalent organic group, Z 1 , Z 2 are each independently a single bond, -NH-, or -O-; R 1 and R 2 each independently represents an alkyl group having 1 to 5 carbon atoms.
[0022] R 1 and R 2Examples of the alkyl group having 1 to 5 carbon atoms represented by include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, an n-pentyl group, an isopentyl group, an s-pentyl group, and a t-pentyl group. Examples of the alkenyl group having 2 to 5 carbon atoms represented by include a vinyl group, an allyl group, a 1-propenyl group, a 1-butenyl group, a 2-butenyl group, a 3-butenyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, and a 4-pentenyl group. Examples of the alkynyl group having 2 to 5 carbon atoms represented by include an ethynyl group, a 1-propynyl group, a 2-propynyl (propargyl) group, a 3-butynyl group, and a pentynyl group. Among these, from the viewpoint of liquid crystal alignment, R 1 and R 2 is preferably a methyl group or an ethyl group, and more preferably a methyl group.
[0023] X 1 , X 2 is a divalent organic group, the structure of which is not particularly limited, but is preferably an organic group having 30 or less carbon atoms. From the viewpoint of liquid crystal alignment, it is preferable that the compound has a phenylene group. A particularly preferred structure is a divalent group represented by the following formula [2-2].
[0024] [ka]
[0025] In the formula, X 3 , X 5 each independently represents a phenylene group which may have a substituent; 4 represents a divalent group having 10 or less carbon atoms; L 1 , L 2 each independently represents a single bond, -O-, or -S-; n1 and n2 each independently represent 0 or 1; *1 and *2 each represent a bonding site. 1 or Z 2 and the other is bonded to a nitrogen atom.
[0026] X 3, X 5 Specific examples of the substituent that the phenylene group may have include alkyl groups and alkoxy groups having 1 to 5 carbon atoms, fluoroalkyl groups and fluoroalkoxy groups having 1 to 5 carbon atoms, and a fluorine atom.
[0027] X 4 Preferred specific examples of the group include divalent groups selected from the following (a) to (d): (a): A group obtained by removing two hydrogen atoms from a hydrocarbon having 1 to 10 carbon atoms. (b): -O-, -S-, -SO- between one or more carbon-carbon bonds of (a). 2 - A group having a structure sandwiching a linking group selected from the above. (c): A group having a structure in which one or more carbon atoms in the above (a) or (b) are replaced with a silicon atom or a nitrogen atom. (d): one or more methylene groups (-CH 2 A group in which the aryl group (-) is replaced with a carbonyl group (-CO-). The "hydrocarbon" in (a) may be a saturated or unsaturated hydrocarbon, and may have a linear or branched chain structure, or a cyclic structure or a structure containing a cyclic structure. In addition, in the above (c), when a structure is created in which a carbon atom is replaced with a nitrogen atom, the original carbon atom is limited to one having a hydrogen atom bonded thereto, and in the structure after replacement with a nitrogen atom, the hydrogen atom is deleted.
[0028] X 1 , X 2 More preferred structures include structures represented by (X-1) to (X-11).
[0029] [ka] (n represents an integer from 1 to 6.)
[0030] In the above formula [1], the tetravalent organic group having an alicyclic structure is not particularly limited in structure, but specific examples include the following formula [Y 1 -1]~Formula [Y 1 -20] can be cited as an example.
[0031] [ka]
[0032] [ka]
[0033] [ka] The formula [Y 1 -1]~Formula [Y 1 -4], R 5 ~R 25 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group, and may be the same or different. 5 ~R 25 is preferably a hydrogen atom, a halogen atom, a methyl group or an ethyl group, more preferably a hydrogen atom or a methyl group.
[0034] Among the above, the formula [Y 1 -1] is preferred, and has the formula [Y 1 Specific examples of the structure of [Y 1 -1-1]~Formula [Y 1 From the viewpoint of the liquid crystal alignment property and the sensitivity of the photoreaction of the liquid crystal alignment agent, a structure represented by the following formula [Y 1 -1-1] is particularly preferred.
[0035] [ka]
[0036] A method for synthesizing the diamine will be described below.
[0037] The method for synthesizing the diamine of the formula [1] includes a first step of obtaining an amine derivative of the formula (13) from an isocyanate compound of the formula (12) or an isocyanate compound, using a tetracarboxylic acid dialkyl ester having an alicyclic structure represented by the following formula (11) as a starting material.
[0038] The method for obtaining an isocyanate compound of formula (12) from a tetracarboxylic acid dialkyl ester having an alicyclic structure of formula (11) is to convert a carboxylic acid (-COOH) of formula (11) into a carboxylic acid azide (-COON 3 ), which is converted to an isocyanate compound (-NCO) via a rearrangement reaction such as the Curtius rearrangement or Schmidt rearrangement; or a Rossen rearrangement method in which an isocyanate compound is produced from a carboxylic acid (-COOH) via a hydroxyamide derivative (-CONHOH, -CONHOTs; Ts is a tosyl group (p-toluenesulfonic acid group)). The isocyanate compound thus produced can be converted to an amine derivative of formula (13) by reacting it with water, tert-butyl alcohol, or the like, and such a compound can be produced directly from the compound of formula (11). R in the compound of formula (13) 31 and R 32 When is a hydrogen atom, that is, when the diisocyanate compound of formula (12) is reacted with water, purification may be facilitated by reacting it with an amino-protecting reagent such as di-tert-butyl dicarbonate, 4-nitrobenzyl chloride, benzyl chloroformate, or fluorenylmethyl chloroformate to obtain an amino-protected product, which may result in easier synthesis.
[0039] [ka]
[0040] [ka]
[0041] [ka]
[0042] In formulas (11) to (13), Y 1 is a divalent organic group having an alicyclic structure, and R 1 and R 2 Each independently represents an alkyl group having 1 to 5 carbon atoms. 31 and R 32 represents a hydrogen atom or an amino-protecting group. Here, R 31 and R 32 Examples of the protecting group for the amino group represented by the formula (I) include, but are not limited to, a benzyl group, a nitrobenzyl group, a CBz group (benzyloxycarbonyl group), a Boc group (tert-butoxycarbonyl group), and an Fmoc group (9-fluorenylmethyloxycarbonyl group).
[0043] The method for synthesizing a diamine compound of the present invention comprises the steps of: reacting an isocyanate compound of formula (12) with HZ 2 -X 2 -N 0 (Z 2 represents -O- or -NH-; X 2 represents a divalent organic group, and N 0 represents a group that can be converted to an amino group. X 2 Specific examples and preferred structures of are the same as those shown in the explanation of formula [1]. ) or alcohol compound represented by formula (13) is reacted with Cl-C(=O)-X 2 -N 0 (X 2 represents a divalent organic group, and N 0 represents a group that can be converted to an amino group. 2 -N 0 (X 2 represents a divalent organic group, and N 0represents a group that can be converted to an amino group.) isocyanate compounds represented by Cl-C(=O)-OX 2 -N 0 (X 2 represents a divalent organic group, and N 0 represents a group that can be converted into an amino group. The method includes a second step of reacting a chloroformic acid derivative represented by formula (14) to obtain a diamine compound precursor represented by formula (14). 0 is a group that can be converted to an amino group, and examples of the protected amino group include a nitro group, a protected amino group, etc. The protected amino group is not particularly limited as long as it can be easily converted to an amino group by deprotection, and examples of the protected amino group include a group in which one hydrogen atom of an amino group is substituted with a benzyl group, a nitrobenzyl group, a CBz group (benzyloxycarbonyl group), a Boc group (tert-butoxycarbonyl group), or an Fmoc group (9-fluorenylmethyloxycarbonyl group).
[0044] [ka] N 0 represents a nitro group or a protected amino group.
[0045] Specific examples of the compound of formula (14) include the following formulas (15) to (17). Here, the compound of formula (15) is a compound having an amino group and a nitro group or a protected amino group in the isocyanate compound of formula (12) (e.g., H 2 NX 2 -N 0 The compound of formula (16) is produced by reacting the isocyanate compound of formula (12) with a compound having a hydroxyl group and a nitro group or a protected amino group (for example, HO-X 2 -N 0 The compound of formula (17) is produced by reacting the diamide compound of formula (13) with an acid chloride compound having a nitro group or a protected amino group, or with a carboxylic acid having a nitro group or a protected amino group in the presence of a suitable condensing agent.
[0046] [ka]
[0047] [ka]
[0048] [ka]
[0049] The method for synthesizing a diamine compound of the present invention includes a third step of converting the nitro group or the protected amino group of the compound of formula (14) to an amino group, thereby producing a diamine compound of formula (1). In the present invention, the first step and the second step can be carried out separately, but the first step and the second step can also be carried out consecutively or as one step.
[0050] <Specific polymer A> The specific polymer A of the present invention is at least one polymer selected from a polyimide precursor containing a structural unit represented by the following formula [3-1] and a polyimide which is an imide compound thereof, and is obtained by reacting a diamine represented by the above formula [1] with a tetracarboxylic acid derivative.
[0051] [ka] In the formula, R 3 and R 4each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. Examples of the alkyl group having 1 to 5 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, an n-pentyl group, an isopentyl group, an s-pentyl group, and a t-pentyl group. Examples of the alkenyl group having 2 to 5 carbon atoms include a vinyl group, an allyl group, a 1-propenyl group, a 1-butenyl group, a 2-butenyl group, a 3-butenyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, and a 4-pentenyl group. Examples of the alkynyl group having 2 to 5 carbon atoms include an ethynyl group, a 1-propynyl group, a 2-propynyl (propargyl) group, a 3-butynyl group, and a pentynyl group. Among these, from the viewpoint of the ease of proceeding of the imidization reaction when heated, R 3 and R 4 is preferably a hydrogen atom, a methyl group or an ethyl group, and more preferably a hydrogen atom or a methyl group.
[0052] V 0 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and its structure is not particularly limited. 0 is appropriately selected depending on the degree of required properties such as the solubility of the polymer in a solvent, the coatability of the liquid crystal alignment agent, the alignment of the liquid crystal when made into a liquid crystal alignment film, the voltage holding rate, the stored charge, etc., and one type may be used in the same polymer, or two or more types may be mixed.
[0053] Examples of the tetracarboxylic acid derivative include tetracarboxylic acid dianhydrides, tetracarboxylic acid dihalide compounds, tetracarboxylic acid dialkyl ester compounds, and tetracarboxylic acid dialkyl ester dihalide compounds. For example, V in the formula [3-1] 0 The tetracarboxylic dianhydride from which this is derived includes the compound represented by the following formula [5].
[0054] [ka] V in formula [3-1] and formula [5] 0Specific examples of the above include Y 1 Specific examples of the tetravalent organic group having an alicyclic structure include those shown in the above formulas and those shown in the following formulas [V-1] to [V-16], but the present invention is not limited to these.
[0055] [ka]
[0056] [ka]
[0057] The specific polymer A of the present invention may contain a structural unit other than the structural unit represented by the above formula [3-1]. For example, the structural unit other than the structural unit represented by the formula [3-1] may be a structural unit represented by the following formula [3-2].
[0058] [ka] In the formula, V 0 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and W 2 is a divalent organic group other than the structure represented by the formula [2-1], and R 3 , R 4 , A 1 and A 2 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. V 0 , R 3 , R 4 Specific examples and preferred structures of the formula [3-1] are the same as those of the formula [3-1]. However, in the embodiment of the present invention, the structural unit represented by the formula [3-1] and the structural unit represented by the formula [3-2] are V 0 , R 3 , R 4 The specific structures of the above do not necessarily have to be the same. A 1 and A 2 Specific examples of the alkyl group having 1 to 5 carbon atoms in R3 and R 4 From the viewpoint of liquid crystal alignment, A 1 and A 2 is preferably a hydrogen atom or a methyl group.
[0059] W 2 is a divalent organic group derived from a diamine other than the diamine represented by the formula [1] (hereinafter, also referred to as other diamine), and its structure is not particularly limited as long as it is a divalent organic group other than the structure represented by the formula [2-1]. Examples of other diamines include compounds represented by the following formula [2-2].
[0060] [ka] W 2 , A 1 and A 2 respectively represent the same as equation [3-2].
[0061] Below, 2 Specific examples of the structure are given below, but the present invention is not limited to these.
[0062] [ka]
[0063] [ka]
[0064] [ka]
[0065] [ka]
[0066] [ka]
[0067]
change
[0068]
change
[0069]
change
[0070]
change
[0071]
change
[0072]
change
[0073]
change
[0074]
change
[0075]
change
[0076]
change
[0077] [ka]
[0078] [ka]
[0079] [ka]
[0080] [ka]
[0081] [ka]
[0082] In addition, the Boc group in the formula represents a tert-butoxycarbonyl group represented by the following formula.
[0083] [ka]
[0084] When the specific polymer A contains a structural unit of the formula [3-2] in addition to the structural unit of the formula [3-1], the structural unit of the formula [3-1] is preferably 10 mol % or more, more preferably 20 mol % or more, and particularly preferably 30 mol % or more, based on the total of the structural units of the formula [3-1] and the structural units of the formula [3-2].
[0085] When a liquid crystal alignment film is obtained from a liquid crystal alignment agent containing the polymer, the molecular weight of the specific polymer A is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and even more preferably 10,000 to 100,000, in terms of weight average molecular weight measured by GPC (Gel Permeation Chromatography) in consideration of the strength of the coating film (liquid crystal alignment film), workability during coating film formation, and uniformity of the coating film.
[0086] <Method of Producing Polymer> Next, a main method for producing the polymer contained in the liquid crystal alignment agent of the present invention will be described. Note that the method described below is a production example, and is not limited thereto.
[0087] For example, when the specific polymer A is a polyamic acid, the polymer can be obtained by reacting a tetracarboxylic acid derivative, tetracarboxylic dianhydride, with a diamine component. A known synthesis method can be used to obtain a polyamic acid by this reaction. The synthesis method is a method in which a tetracarboxylic dianhydride is reacted with a diamine component in an organic solvent. This method is advantageous in that it proceeds relatively easily in an organic solvent and does not generate by-products.
[0088] The organic solvent used in the above reaction is not particularly limited as long as it dissolves the produced polyamic acid (polymer). Examples of the organic solvent include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methylcaprolactam, dimethylsulfoxide, tetramethylurea, pyridine, dimethylsulfone, hexamethylsulfoxide, γ-butyrolactone, isopropyl alcohol, methoxymethylpentanol, dipentene, ethyl amyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isoamyl ketone, methyl isopropyl ketone, methyl cellosolve, ethyl cellosolve, methyl cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol-tert-butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene glycol monoacetate, diethylene glycol dimethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3- Methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methylcyclohexene, propyl ether, dihexyl ether, dioxane, n-hexane, n-pentane, n-octane, diethyl ether, cyclohexanone, ethylene carbonate, propylene carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate,Examples of the solvent include methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, diglyme, 4-hydroxy-4-methyl-2-pentanone, 3-methoxy-N,N-dimethylpropanamide, 3-ethoxy-N,N-dimethylpropanamide, and 3-butoxy-N,N-dimethylpropanamide. These may be used alone or in combination. In addition, even if the solvent does not dissolve polyamic acid (polymer), it may be mixed with the organic solvent as long as the generated polyamic acid does not precipitate. In particular, moisture in the organic solvent inhibits the polymerization reaction and further causes hydrolysis of the generated polyamic acid, so it is preferable to use the organic solvent that has been dehydrated and dried as much as possible.
[0089] When reacting the tetracarboxylic dianhydride with the diamine component in an organic solvent, any of the following methods may be used: a method in which a solution in which the diamine component is dispersed or dissolved in an organic solvent is stirred, and the tetracarboxylic dianhydride is added as is or after being dispersed or dissolved in an organic solvent; a method in which the diamine component is added to a solution in which the tetracarboxylic dianhydride is dispersed or dissolved in an organic solvent; a method in which the tetracarboxylic dianhydride and the diamine component are added alternately; etc. In addition, when the tetracarboxylic dianhydride or the diamine component is composed of a plurality of kinds of compounds, they may be reacted in a premixed state, or may be reacted individually in sequence, and low molecular weight compounds that have been reacted individually may be mixed and reacted to form a high molecular weight compound.
[0090] The polycondensation temperature can be selected from -20°C to 150°C, but is preferably in the range of -5°C to 100°C. The polycondensation reaction can be carried out at any concentration, but if the concentration is too low, it becomes difficult to obtain a polymer with a high molecular weight, and if the concentration is too high, the viscosity of the reaction solution becomes too high, making uniform stirring difficult. Therefore, the total concentration of the tetracarboxylic dianhydride and diamine components in the reaction solution is preferably 1 to 50% by mass, more preferably 5 to 30% by mass. The reaction may be carried out at a high concentration in the early stage, and then an organic solvent may be added.
[0091] In the polymerization reaction of polyamic acid, the ratio of the total number of moles of tetracarboxylic dianhydride to the total number of moles of diamine components (total number of moles of tetracarboxylic dianhydride / total number of moles of diamine components) is preferably 0.8 to 1.2. As in the case of a normal polycondensation reaction, the closer this molar ratio is to 1.0, the higher the molecular weight of the polyamic acid produced will be.
[0092] When the specific polymer A is a polyamic acid ester, it can be obtained by reacting a tetracarboxylic acid diester dichloride with a diamine component, or by reacting a tetracarboxylic acid diester with a diamine component in the presence of a suitable condensing agent or base, or by synthesizing a polyamic acid in advance by the above-mentioned method and esterifying the carboxylic acid in the amic acid by utilizing a polymer reaction.
[0093] Specifically, for example, a polyamic acid ester can be synthesized by reacting a tetracarboxylic acid diester dichloride with a diamine in the presence of a base and an organic solvent at −20° C. to 150° C., preferably 0° C. to 50° C., for 30 minutes to 24 hours, preferably 1 hour to 4 hours.
[0094] As the base, pyridine, triethylamine, 4-dimethylaminopyridine, etc. can be used, but pyridine is preferred because the reaction proceeds mildly. The amount of base added is preferably 2 to 4 times the molar amount of tetracarboxylic acid diester dichloride, from the viewpoints of easy removal and easy production of a high molecular weight substance.
[0095] In addition, when a tetracarboxylic acid diester and a diamine component are polycondensed in the presence of a condensing agent, triphenyl phosphite, dicyclohexylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-carbonyldiimidazole, dimethoxy-1,3,5-triazinylmethylmorpholinium, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, (2,3-dihydro-2-thioxo-3-benzoxazolyl)diphenylphosphonate, 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)4-methoxymorpholinium chloride n-hydrate, or the like can be used as a base.
[0096] In the method using the condensing agent, the reaction proceeds efficiently by adding a Lewis acid as an additive. The Lewis acid is preferably a lithium halide such as lithium chloride or lithium bromide. The amount of Lewis acid added is preferably 0.1 to 1.0 times by molar amount relative to the diamine or tetracarboxylic acid diester to be reacted.
[0097] The solvent used in the above reaction can be the same as the solvent used in synthesizing the polyamic acid shown above, but N-methyl-2-pyrrolidone and γ-butyrolactone are preferred in terms of the solubility of the monomer and polymer, and these may be used alone or in combination of two or more. The concentration during synthesis is preferably 1% by mass to 30% by mass, more preferably 5% by mass to 20% by mass, in terms of the total concentration of the tetracarboxylic acid derivative such as tetracarboxylic acid diester dichloride or tetracarboxylic acid diester and the diamine component in the reaction solution, from the viewpoint of preventing the precipitation of the polymer and facilitating the production of a high molecular weight product. In addition, in order to prevent hydrolysis of the tetracarboxylic acid diester dichloride, it is preferable that the solvent used in the synthesis of the polyamic acid ester is as dehydrated as possible, and it is preferable to prevent the inclusion of outside air in a nitrogen atmosphere.
[0098] When the specific polymer A is a polyimide, it is obtained by ring-closing imidization of a polyimide precursor such as a polyamic acid or a polyamic acid ester. In this polyimide, the ring-closing rate (imidization rate) does not necessarily have to be 100% and can be arbitrarily adjusted depending on the application or purpose.
[0099] Methods for imidizing polyamic acid include thermal imidization in which a solution of polyamic acid is heated as is, and catalytic imidization in which a catalyst is added to a solution of polyamic acid.
[0100] The temperature when thermally imidizing the polyamic acid in a solution is 100° C. to 400° C., preferably 120° C. to 250° C., and it is preferable to carry out the imidization while removing water generated by the imidization reaction from the system.
[0101] The catalytic imidization of polyamic acid can be carried out by adding a basic catalyst and an acid anhydride to a solution of polyamic acid and stirring at -20°C to 250°C, preferably 0°C to 180°C. The amount of the basic catalyst is 0.5 to 30 times by mol, preferably 2 to 20 times by mol, the amount of the acid anhydride is 1 to 50 times by mol, preferably 3 to 3 .... Examples of the basic catalyst include pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc., among which pyridine is preferred because it has a suitable basicity for promoting the reaction. Examples of the acid anhydride include acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc., among which acetic anhydride is preferred because it is easy to purify after the reaction. The imidization rate by catalytic imidization can be controlled by adjusting the amount of the catalyst, the reaction temperature, and the reaction time.
[0102] As described above, a polyimide can also be obtained by heating a polyamic acid ester at a high temperature to promote removal of alcohol and ring closure.
[0103] In addition, when recovering the generated polyamic acid, polyamic acid ester, or polyimide from a polyimide precursor such as polyamic acid or polyamic acid ester, or a reaction solution of polyimide, the reaction solution may be poured into a poor solvent to cause precipitation. Examples of poor solvents used for precipitation include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, water, etc. The polyimide precursor or polyimide precipitated by pouring into a poor solvent can be recovered by filtration, and then dried at room temperature or by heating under normal pressure or reduced pressure. In addition, the polyimide precursor or polyimide precipitated and recovered can be redissolved in an organic solvent and the reprecipitation recovery operation repeated 2 to 10 times to reduce impurities in the polymer. Examples of poor solvents in this case include alcohols, ketones, and hydrocarbons, and it is preferable to use three or more poor solvents selected from these because the efficiency of purification is further improved.
[0104] The polymer of the present invention thus obtained can be dissolved in a predetermined organic solvent and used as a liquid crystal alignment agent. This liquid crystal alignment agent is used for a liquid crystal alignment film that controls the alignment of liquid crystal molecules in a liquid crystal layer in a liquid crystal display element. The liquid crystal alignment agent containing the polymer of the present invention will be described below.
[0105] <Liquid crystal alignment agent> The liquid crystal aligning agent of the present invention contains at least one polymer selected from the specific polymer A.
[0106] However, the polymers contained in the liquid crystal aligning agent of the present invention may all be the specific polymer A of the present invention, or may contain two or more different structures of the specific polymer A of the present invention. Alternatively, in addition to the specific polymer A of the present invention, other polymers may be contained. Examples of the other polymers include polyamic acid, polyimide, polyamic acid ester, polyester, polyamide, polyurea, polyorganosiloxane, cellulose derivatives, polyacetal, polystyrene or its derivatives, poly(styrene-phenylmaleimide) derivatives, poly(meth)acrylates, etc. Among these, polyamic acid is preferable. The polyamic acid as the other polymer is, for example, 3 , R 4 In particular, the polyamic acid having a structural unit in which W is a hydrogen atom is included in the formula [3-2]. 2 It is preferable to mix a polyamic acid having a nitrogen atom bonded to a nitrogen-containing aromatic heterocycle or an aromatic group into the liquid crystal aligning agent of the present invention from the viewpoint of improving the relaxation speed of accumulated charges in a liquid crystal display element produced using the liquid crystal aligning agent of the present invention.
[0107] When the liquid crystal aligning agent of the present invention contains other polymers, the ratio of the polymer of the present invention to the total polymer components is preferably 5% by mass or more, for example, 5 to 95% by mass. The ratio of the polymer of the present invention can be appropriately selected depending on the properties of the liquid crystal aligning agent and the liquid crystal alignment film.
[0108] The liquid crystal aligning agent of the present invention is used to prepare a liquid crystal alignment film, and generally takes the form of a coating liquid from the viewpoint of forming a uniform thin film. The liquid crystal aligning agent of the present invention is also preferably a coating liquid containing the above-mentioned polymer component and an organic solvent that dissolves the polymer component. In this case, the concentration of the polymer in the liquid crystal aligning agent can be appropriately changed depending on the thickness of the coating film to be formed. From the viewpoint of forming a uniform and defect-free coating film, it is preferably 1% by mass or more, and from the viewpoint of storage stability of the solution, it is preferably 10% by mass or less. A particularly preferred polymer concentration is 2 to 8% by mass.
[0109] The organic solvent contained in the liquid crystal alignment agent of the present invention is not particularly limited as long as it is an organic solvent that dissolves the polymer. Specific examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethylsulfoxide, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, and the like. Among them, it is preferable to use N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and γ-butyrolactone. The organic solvents exemplified here may be used alone or in a mixture. Furthermore, even if the solvent does not dissolve the polymer, it may be mixed with the organic solvent to the extent that the generated polymer does not precipitate.
[0110] In addition, the organic solvent contained in the liquid crystal alignment agent is generally a mixed solvent containing a solvent that improves the coating property and the surface smoothness of the coating film when applying the liquid crystal alignment agent in addition to the above-mentioned solvent, and such a mixed solvent is preferably used in the liquid crystal alignment agent of the present invention. Specific examples of the organic solvent to be used in combination are listed below, but are not limited thereto.
[0111] For example, ethanol, isopropyl alcohol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentyl alcohol, tert-pentyl alcohol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-Octanol, 2-Ethyl-1-hexanol, Cyclohexanol, 1-Methylcyclohexanol, 2-Methylcyclohexanol, 3-Methylcyclohexanol, 1,2-Ethanediol, 1,2-Propanediol, 1,3-Propanediol, 1,2-Butanediol, 1,3-Butanediol, 1,4-Butanediol, 2,3-Butanediol, 1,5-Pentanediol, 2-Methyl-2,4-Pentanediol, 2-Ethyl-1,3-Hexanediol, Dipropyl Ether, Dibutyl Ether, Dihexyl Ether, Di Oxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethyl Butyl acetate, 2-ethylhexyl acetate, ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, ethylene glycol monobutyl ether, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, propylene glycol monobutyl ether, 1-(butoxyethoxy)propanol,Propylene glycol monomethyl ether acetate, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate Examples of the solvent include tartrate, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, and isoamyl lactate.
[0112] In addition to the above-mentioned solvents, for example, the solvents represented by the following formulas [S-1] to [S-3] can be used.
[0113] [ka] In formula [S-1] and formula [S-2], R 28 and R 29 represents an alkyl group having 1 to 3 carbon atoms. Examples of the alkyl group having 1 to 3 carbon atoms include a methyl group, an ethyl group, an n-propyl group, and an isopropyl group. In addition, in the formula [S-3], R 30represents an alkyl group having 1 to 4 carbon atoms. Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, and a tert-butyl group.
[0114] Among the organic solvents used in combination, 1-hexanol, cyclohexanol, 1,2-ethanediol, 1,2-propanediol, propylene glycol monobutyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monobutyl ether, or dipropylene glycol dimethyl ether is preferably used. The type and content of such a solvent are appropriately selected depending on the coating device, coating conditions, coating environment, etc. of the liquid crystal alignment agent.
[0115] Moreover, these solvents preferably account for 20% by mass to 99% by mass of the total solvent contained in the liquid crystal alignment agent, more preferably 20% by mass to 90% by mass, and even more preferably 20% by mass to 70% by mass.
[0116] The liquid crystal alignment agent of the present invention may additionally contain components other than the polymer component and the organic solvent. Examples of such additional components include adhesion assistants for increasing the adhesion between the liquid crystal alignment film and the substrate or between the liquid crystal alignment film and the sealant, crosslinking agents for increasing the strength of the liquid crystal alignment film, and dielectrics and conductive materials for adjusting the dielectric constant and electrical resistance of the liquid crystal alignment film. Specific examples of these additional components are as disclosed in various known documents related to liquid crystal alignment agents, but if one example is to be given, the components disclosed in paragraphs
[0105] to
[0116] of International Publication No. 2015 / 060357 can be mentioned.
[0117] <Liquid crystal alignment film> The liquid crystal alignment film of the present invention is obtained from the liquid crystal alignment agent described above. One example of a method for obtaining a liquid crystal alignment film from a liquid crystal alignment agent is to apply a liquid crystal alignment agent in the form of a coating liquid to a substrate, dry, and bake the resulting film, and then perform an alignment treatment by a rubbing treatment method or a photo-alignment treatment method.
[0118] The substrate to which the liquid crystal alignment agent of the present invention is applied is not particularly limited as long as it is a highly transparent substrate, and plastic substrates such as acrylic substrates and polycarbonate substrates can be used in addition to glass substrates and silicon nitride substrates. In this case, it is preferable to use a substrate on which an ITO electrode or the like for driving the liquid crystal is formed in terms of simplifying the process. In addition, in a reflective liquid crystal display element, an opaque material such as a silicon wafer can be used for only one substrate, and in this case, a light-reflecting material such as aluminum can be used for the electrode.
[0119] The method for applying the liquid crystal alignment agent is not particularly limited, but industrially, screen printing, offset printing, flexographic printing, inkjet printing, etc. are generally used. Other application methods include a dip method, a roll coater method, a slit coater method, a spinner method, a spray method, etc., and these may be used depending on the purpose.
[0120] After the liquid crystal alignment agent is applied onto the substrate, the substrate is baked at 50 to 300°C, preferably 80 to 250°C, by a heating means such as a hot plate, a hot air circulation oven, or an infrared oven, to evaporate the solvent and form a coating film (liquid crystal alignment film). The thickness of the coating film formed after baking is preferably 5 nm to 300 nm, more preferably 10 nm to 100 nm, since if it is too thick, it is disadvantageous in terms of power consumption of the liquid crystal display element, and if it is too thin, the reliability of the liquid crystal display element may decrease. When the liquid crystal is to be horizontally or obliquely aligned, the coating film after baking is treated by rubbing or irradiation with polarized ultraviolet light, etc.
[0121] After the liquid crystal alignment agent is applied onto the substrate, the solvent is evaporated and the substrate is baked using a heating means such as a hot plate, a heat circulation oven, or an IR (infrared) oven. The temperature and time for the drying and baking process after the liquid crystal alignment agent is applied can be selected as desired. Usually, the substrate is baked at 50°C to 120°C for 1 to 10 minutes, and then baked at 150°C to 300°C for 5 to 120 minutes to sufficiently remove the solvent contained therein.
[0122] The liquid crystal alignment film of the present invention is suitable as a liquid crystal alignment film for a liquid crystal display element of a horizontal electric field mode such as an IPS mode or an FFS mode, and is particularly useful as a liquid crystal alignment film for a liquid crystal display element of an FFS mode.
[0123] <Liquid crystal display element> The liquid crystal display element of the present invention is provided with the above-mentioned liquid crystal alignment film, and is obtained by preparing a substrate with a liquid crystal alignment film obtained from the above-mentioned liquid crystal alignment agent, and then preparing a liquid crystal cell by a known method, and using the liquid crystal cell to form an element. One example is a liquid crystal display element provided with a liquid crystal cell having two substrates arranged to face each other, a liquid crystal layer provided between the substrates, and a liquid crystal alignment film formed by the liquid crystal alignment agent of the present invention and provided between the substrates and the liquid crystal layer.
[0124] The substrate used in the liquid crystal display element of the present invention is not particularly limited as long as it is a highly transparent substrate, but is usually a substrate on which a transparent electrode for driving the liquid crystal is formed. Specific examples include the same substrates as those described above for the liquid crystal alignment film.
[0125] The liquid crystal alignment film is formed by applying the liquid crystal aligning agent of the present invention onto the substrate and then baking the same, as described above in detail.
[0126] The liquid crystal material constituting the liquid crystal layer of the liquid crystal display element of the present invention is not particularly limited, and examples thereof include nematic liquid crystal and smectic liquid crystal, among which nematic liquid crystal is preferred, and either positive type liquid crystal material or negative type liquid crystal material may be used. Specifically, for example, MLC-2003, MLC-6608, MLC-6609, MLC-3019, MLC-2041, MLC-7026-100, etc. manufactured by Merck can be used.
[0127] Specifically, transparent glass substrates are prepared, and a common electrode is provided on one substrate, and segment electrodes are provided on the other substrate. These electrodes can be, for example, ITO electrodes, and are patterned so as to display a desired image. Next, an insulating film is provided on each substrate so as to cover the common electrode and segment electrodes. The insulating film can be, for example, a SiO 2 -TiO 2 Next, a liquid crystal alignment film is formed on each substrate under the above-mentioned conditions.
[0128] Next, a sealant, for example an ultraviolet-curable sealant, is placed at a predetermined location on one of the two substrates on which the liquid crystal alignment film is formed, and liquid crystal is placed at several predetermined locations on the liquid crystal alignment film surface.The other substrate is then attached and pressed together so that the liquid crystal alignment film faces the other substrate, spreading the liquid crystal over the front surface of the liquid crystal alignment film.Then, ultraviolet light is irradiated onto the entire surface of the substrate to cure the sealant, thereby obtaining a liquid crystal cell.
[0129] Alternatively, as a process after forming a liquid crystal alignment film on the substrate, when placing a sealant at a predetermined position on one of the substrates, an opening into which liquid crystal can be filled from the outside is provided, and after bonding the substrates together without placing liquid crystal, liquid crystal material is injected into the liquid crystal cell through the opening provided in the sealant, and then this opening is sealed with an adhesive to obtain a liquid crystal cell. The liquid crystal material can be injected by a vacuum injection method or a method utilizing capillary action in the atmosphere.
[0130] In any of the above methods, in order to secure space within the liquid crystal cell into which the liquid crystal material is filled, it is preferable to take measures such as providing columnar protrusions on one of the substrates, scattering spacers on one of the substrates, mixing spacers into the sealing agent, or a combination of these.
[0131] Next, polarizing plates are provided. Specifically, it is preferable to attach a pair of polarizing plates to the surfaces of the two substrates opposite to the liquid crystal layer.
[0132] The liquid crystal alignment film and liquid crystal display element of the present invention are not limited to the above description as long as the liquid crystal alignment agent of the present invention is used, and may be produced by other known methods. The process of obtaining a liquid crystal display element from a liquid crystal alignment agent is disclosed in, for example, paragraphs
[0074] to
[0081] of JP2015-135393A, as well as many other documents.
[0133] As described above, the liquid crystal display element produced by using the liquid crystal aligning agent of the present invention has excellent reliability and can be suitably used for large-screen, high-definition liquid crystal televisions and the like. EXAMPLES
[0134] The present invention will be described in more detail below with reference to examples, but the present invention should not be construed as being limited to these examples.
[0135] The general-purpose solvents used to dissolve the materials used in the examples and the chemical structural formulas of the monomers that are the raw materials for the materials used in the examples are as follows: NMP: N-methyl-2-pyrrolidone GBL: Gamma butyrolactone BCS: Butyl cellosolve DC-1: 1,3-Dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride DC-2: Bicyclo[3,3,0]octane-2,4,6,8-tetracarboxylic dianhydride DC-3: 1,2,3,4-Cyclobutanetetracarboxylic dianhydride DC-4: Pyromellitic anhydride DC-5: Tetrahydro-1H-5,9-methanopyrano[3,4-d]oxepin-1,3,6,8(4H)-tetraone DA-1: Dimethyl 2,4-bis((4-aminobenzamido)cyclobutane-1,3-dicarboxylate DA-2: Dimethyl 2,4-bis((4-aminophenyl)carbamoyl)cyclobutane-1,3-dicarboxylate DA-3: 1,2-bis(4-aminophenoxy)ethane DA-4: 1,2-bis(4-aminophenoxy)hexane DA-5: 1-tert-butoxycarbonyl-1,3-bis(4-aminophenethyl)urea DA-6: Dimethyl 2,4-bis((4-aminophenyl)ureido)cyclobutane-1,3-dicarboxylate
[0136] [ka]
[0137] [ka]
[0138] The methods for synthesizing the materials used in the examples and the methods for measuring the properties thereof are as follows.
[0139] [viscosity] In the synthesis examples, the viscosity of the polyamic acid solution was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample amount of 1.1 mL, a cone rotor TE-1 (1°34', R24), and a temperature of 25°C.
[0140] [Molecular weight] The molecular weight was measured by a GPC (gel permeation chromatography) device, and the number average molecular weight (Mn) and weight average molecular weight (Mw) were calculated as polyethylene glycol and polyethylene oxide equivalent values.
[0141] GPC equipment: Shodex (GPC-101), column: Shodex (KD803, KD805 in series), column temperature: 50°C, eluent: N,N-dimethylformamide (additive: lithium bromide monohydrate (LiBr H 2 O) 30mmol / L, phosphoric acid anhydrous crystals (o-phosphoric acid) 30mmol / L, tetrahydrofuran (THF) 10ml / L, flow rate: 1.0ml / min Standard samples for creating a calibration curve: TSK standard polyethylene oxide manufactured by Tosoh Corporation (weight average molecular weight (Mw) approximately 900,000, 150,000, 100,000, 30,000), and polyethylene glycol manufactured by Polymer Laboratory Co., Ltd. (peak top molecular weight (Mp) approximately 12,000, 4,000, 1,000). In order to avoid overlapping peaks, measurements were performed separately on two samples: a sample made by mixing four types of 900,000, 100,000, 12,000, and 1,000, and a sample made by mixing three types of 150,000, 30,000, and 4,000.
[0142] [Measurement of imidization rate] 20 mg of polyimide powder was placed in an NMR sample tube (NMR sampling tube standard, φ5 (Kusano Scientific Co., Ltd.)), deuterated dimethyl sulfoxide (DMSO-d6, 0.05% TMS (tetramethylsilane) mixture) (0.53 ml) was added, and the mixture was sonicated to completely dissolve. This solution was measured by 500 MHz proton NMR using an NMR measurement device (JNW-ECA500) (JEOL Datum Co., Ltd.). The imidization rate was calculated by the following formula using the proton derived from the structure that does not change before and after imidization as the reference proton and the peak integrated value of this proton and the proton peak integrated value derived from the NH group of the amic acid that appears around 9.5 ppm to 11.0 ppm. However, the imidization rate calculated by the following formula is a value when the proton peak derived from the NH group contained in the monomer that is not involved in the polymerization reaction is excluded.
[0143] Imidization rate (%) = (1-α·x / y) × 100
[0144] In the above formula, x is the integrated value of the proton peak derived from the NH group of the amic acid, y is the integrated value of the peak of the reference proton, and α is the ratio of the number of reference protons to one NH group proton of the amic acid in the case of polyamic acid (imidization rate 0%).
[0145] [Fabrication of liquid crystal cells for FFS mode] A liquid crystal cell having a fringe field switching (FFS) mode liquid crystal display element configuration is fabricated.
[0146] First, a substrate with electrodes was prepared. The substrate was a glass substrate with a size of 30 mm x 35 mm and a thickness of 0.7 mm. An ITO electrode with a solid pattern was formed on the substrate as the first layer, which constituted the counter electrode. A SiN (silicon nitride) film formed by a CVD method was formed on the first layer of the counter electrode as the second layer. The thickness of the second layer of the SiN film was 500 nm, and it functions as an interlayer insulating film. A comb-shaped pixel electrode formed by patterning the ITO film as the third layer was arranged on the second layer of the SiN film, forming two pixels, a first pixel and a second pixel. The size of each pixel was about 10 mm in length and about 5 mm in width. At this time, the first layer of the counter electrode and the third layer of the pixel electrode were electrically insulated by the action of the second layer of the SiN film.
[0147] The pixel electrode of the third layer has a comb-like shape formed by arranging multiple electrode elements each having a bent L-shape at the center. The width of each electrode element in the short direction is 3 μm, and the distance between the electrode elements is 6 μm. Since the pixel electrode forming each pixel is formed by arranging multiple electrode elements each having a bent L-shape at the center, the shape of each pixel is not rectangular, but has a shape resembling a bold L-shape that is bent at the center like the electrode elements. Each pixel is divided into upper and lower parts by the bent part at the center, and has a first region above the bent part and a second region below the bent part.
[0148] Comparing the first and second regions of each pixel, the directions of the electrode elements of the pixel electrodes that compose them are different. That is, based on the polarization direction of linearly polarized ultraviolet (LPUV) light of the liquid crystal alignment film described later, the electrode elements of the pixel electrodes in the first region of the pixel are formed to form an angle of +80° (clockwise), and the electrode elements of the pixel electrodes in the second region of the pixel are formed to form an angle of -80° (counterclockwise). That is, the first and second regions of each pixel are configured such that the directions of rotational movement (in-plane switching) of the liquid crystal in the substrate plane induced by application of a voltage between the pixel electrode and the counter electrode are opposite to each other.
[0149] Next, the liquid crystal alignment agent was filtered through a 1.0 μm filter, and then spin-coated on the prepared substrate with electrodes and a glass substrate having a columnar spacer with a height of 4 μm and an ITO film formed on the back side. The coating surface was dried on a hot plate at 80° C. for 2 minutes, and linearly polarized ultraviolet light with a wavelength of 254 nm and an extinction ratio of 26:1 or more was irradiated through a polarizing plate, and then baked in a hot air circulation oven at 230° C. for 30 minutes to form a coating film with a thickness of 100 nm. The above two substrates were combined into a set, a sealant was printed on the substrate, and the other substrate was attached so that the liquid crystal alignment film surfaces faced each other and the alignment direction was 0°, and then the sealant was cured to prepare an empty cell. Liquid crystal MLC-3019 (manufactured by Merck) was injected into this empty cell by a reduced pressure injection method, and the injection port was sealed to obtain an FFS-driven liquid crystal cell.
[0150] [Afterimage evaluation] The polarizers were arranged so that the angle between the two polarizers was 90°, and this state was called crossed Nicols. The liquid crystal cell for evaluating the afterimage described above was placed between these two polarizers, and the orientation state of the injected liquid crystal was observed. The specific evaluation method was to determine whether the injected liquid crystal was uniformly oriented in the liquid crystal cell. If the liquid crystal in the liquid crystal cell was not uniformly oriented, bright lines were observed, and a clear bright / dark field could not be observed depending on the angle between the two polarizers and the orientation direction of the liquid crystal. On the other hand, if the liquid crystal in the liquid crystal cell was uniformly oriented, bright lines were not observed, and a clear bright / dark field could be observed depending on the angle between the two polarizers and the orientation direction of the liquid crystal. As evaluation criteria, if the above bright lines were not observed at all and a clear bright / dark field was observed, it was rated as "good," if a clear bright / dark field could be observed but only a slight bright line was observed, it was rated as "fair," and if a clear bright / dark field could not be observed and a clear bright line was observed, it was rated as "poor."
[0151] [Display failure evaluation] The liquid crystal cell prepared above was evaluated for display defects. The evaluation was performed by heating the liquid crystal cell prepared above in a heating oven at 60°C for more than two weeks, and then observing it with a polarizing microscope (ECLIPSE E600WPOL) (Nikon Corporation). Specifically, the liquid crystal cell was placed in cross-Nicols with respect to the polarizer, observed with a polarizing microscope with a lens magnification of 5 times, and the number of confirmed bright spots was counted, with less than 5 bright spots being rated as "good" and more than 5 being rated as "bad."
[0152] [Liquid crystal alignment evaluation] The alignment of the liquid crystal cells prepared above was evaluated. As an evaluation method, the liquid crystal cells were placed under crossed Nicols polarizers in a state where the luminance was at its lowest, and the alignment state was compared immediately after preparation and after realignment treatment (heating at 110°C for 1 hour and returning to room temperature). If no flow alignment or domains were observed immediately after preparation of the liquid crystal cell, it was marked as ◯; if flow alignment or domains disappeared during the realignment treatment, it was marked as △; if the alignment defects were observed even after realignment, it was marked as ×.
[0153] "Monomer synthesis example" Synthesis Example 1 Synthesis of Dimethyl 2,4-bis(3-(4-aminophenyl)ureido)cyclobutane-1,3-dicarboxylate
[0154] [ka]
[0155] <1st process> Synthesis of dimethyl 2,4-bis(3-(4-nitrophenyl)ureido)cyclobutane-1,3-dicarboxylate In a 1L 4-neck flask equipped with a nitrogen inlet tube, bis(methoxycarbonyl)cyclobutane-1,3-dicarboxylic acid (100.0 g: 384.23 mmol) was weighed out, toluene (500.0 g) was added, triethylamine (97.2 g: 960.58 mmol), and diphenylphosphoryl azide [DPPA] (232.6 g: 845.31 mmol) were added, and the mixture was stirred at room temperature under a nitrogen atmosphere for 30 minutes, then heated to 60°C and reacted for another 3 hours. As the reaction proceeded, gas was generated, and it was confirmed that the gas generation had stopped. The reaction solution was returned to room temperature, 1,4diaza-bicyclo[2.2.2]octane[DABCO] (2.15g:19.21mmol), 4-Nitroaniline (116.76g:845.31mmol), and tetrahydrofuran (200.0g) were added, and the temperature was raised to 60°C again, and the reaction was carried out for 24 hours under a nitrogen atmosphere. After confirming the disappearance of the raw materials by TLC, the reaction solution was transferred to a separatory funnel. At this time, the organic layer was separated into two layers, so the lower layer was separated and poured into methanol and stirred, and a solid precipitated. This solid was collected by filtration. One of the upper layers was washed three times with 100ml of pure water, and the organic layer was subjected to solvent distillation using a rotary evaporator, and a solid precipitated. This crude product was collected, mixed with the solid obtained above, heated and washed twice with methanol (300.0 g) (reflux: 1 hour), and vacuum dried to obtain a pale yellow solid (136.56 g: yield 67%). The structure was confirmed by nuclear magnetic resonance spectroscopy [1 H-NMR (400 MHz) was performed to confirm that it was the desired compound. The measurement data are shown below.
[0156] 1 H-NMR(400MHz:D6-DMSO)δ:9.34(s:2H), 8.11(q:4H), 7.60(q:4H), 7.04(d:2H), 4.78(q:2H), 4.07(m:2H), 3.60(s:6H)
[0157] <Second process> Synthesis of Dimethyl 2,4-bis(3-(4-amonophenyl)ureido)cyclobutane-1,3-dicarboxylate The dimethyl 2,4-bis(3-(4-nitro-phenyl)ureido)-cyclobutane-1,3-dicarboxylate (100.0 g: 188.52 mmol) obtained by the above operation, 10% palladium carbon (10.0 g), and thoroughly degassed N,N-dimethylformamide (500.0 g) were added to a 1 L four-neck flask, hydrogen gas was replaced, and the mixture was reacted for 24 hours at 60 ° C with vigorous stirring. After confirming the disappearance of the raw materials, the palladium carbon was removed by filtration in a hot state, and activated carbon (30 g) was added, and the mixture was stirred at 60 ° C for 3 hours and filtered while hot. The filtrate was poured into 1 L of methanol, and a solid precipitated when stirred for a while at 10 ° C. The obtained solid was collected by filtration, washed twice with 300.0 g of methanol, and dried in vacuum to obtain 74.5 g of the target milky white solid. The structure was confirmed by nuclear magnetic resonance spectroscopy [ 1 H-NMR (400 MHz) was performed to confirm that it was the desired compound. The measurement data are shown below.
[0158] 1 H-NMR(400MHz:D6-DMSO)δ:8.01(s:4H), 6.95(q:4H), 6.49(d:2H), 6.45(q:4H), 4.75(q:2H), 4.73(br:4H), 3.64(s:6H),3.35(m:2H)
[0159] Synthesis Example 2 Synthesis of Dimethyl 2,4-bis(4-aminobenzamido)cyclobutane-1,3-dicarboxylate
[0160] [ka]
[0161] <1st process> Synthesis of dimethyl 2,4-bis((tert-butoxycarbonyl)amino)cyclobutane-1,3-dicarboxylate In a 2L 4-neck flask equipped with a nitrogen inlet tube, bis(methoxycarbonyl)cyclobutane-1,3-dicarboxylic acid (100g: 418mmol) was weighed out, toluene (1000g) was added, triethylamine (92.0g: 916mmol), and diphenylphosphoryl azide [DPPA] (252g: 916mmol) were added, and the mixture was stirred at room temperature for 30 minutes under a nitrogen atmosphere, then heated to 60°C and reacted for another 3 hours. Gas was generated as the reaction proceeded, and it was confirmed that the gas generation had stopped. The reaction solution was cooled to room temperature, and 1,4diaza-bicyclo[2.2.2]octane [DABCO] (2.35: 20.9mmol), tert-butyl alcohol (155g: 2.09×10 3 The mixture was heated to 80°C and stirred under nitrogen for 24 hours. After the reaction was completed, the reaction solution was cooled to -20°C and the product was recrystallized. The solid was recrystallized using ethyl acetate as a good solvent and hexane as a poor solvent, and then dried in vacuum to obtain the desired white solid (60.0 g: 145 mmol, yield: 35%). The structure of the product was confirmed by nuclear magnetic resonance spectroscopy [ 1 H-NMR (400 MHz) was performed to confirm that it was the desired compound. The measurement data are shown below.
[0162] 1H-NMR(400MHz:D6-DMSO)δ:7.40-7.38(ss:2H), 4.51-4.49(q:2H), 3.56(s:6H), 3.42-3.38(q:2H), 1.36(s:18H)
[0163] <Second process> Synthesis of Dimethyl 2,4-bis(4-nitrobenzamido)cyclobutane-1,3-dicarboxylate Dimethyl 2,4-bis((tert-butoxycarbonyl)amino)cyclobutane-1,3-dicarboxylate (60.0 g: 145 mmol) obtained in the above procedure was weighed into a 2 L four-neck flask equipped with a nitrogen inlet tube, chloroform (600.0 g) was added, and trifluoroacetic acid [TFA] (164 g: 1.45 × 10 3 The reaction solution was cooled to about 0°C, triethylamine (32.1 g: 318 mmol) was added, and the mixture was stirred at room temperature for 0.5 hours. Then, 4-nitrobenzoic acid chloride (67.0 g: 602 mmol) dissolved in 670 g of chloroform was gently added dropwise, and the mixture was stirred at room temperature for 6 hours. After the reaction was completed, the reaction solution was concentrated, washed three times with 200 ml of pure water, and once with 200 ml of saturated saline. The mixture was then recrystallized using chloroform as a good solvent and hexane as a poor solvent, and the resulting solid was dried in vacuum to obtain the desired pale yellow solid (56.0 g, 112 mmol). The structure of the product was confirmed by nuclear magnetic resonance spectroscopy [ 1 H-NMR (400 MHz) was performed to confirm that it was the desired compound. The measurement data are shown below.
[0164] 1 H-NMR(400MHz:D6-DMSO)δ:9.29-9.27(d:2H), 8.37(dd:4H), 8.06(dd:4H), 5.23-5.17(m:2H), 3.86-3.82(m:2H), 3.55(s:6H)
[0165] <3rd process> Synthesis of Dimethyl 2,4-bis(4-aminobenzamido)cyclobutane-1,3-dicarboxylate The dimethyl 2,4-bis(4-nitrobenzamido)cyclobutane-1,3-dicarboxylate (20.0 g: 112 mmol) obtained by the above operation, activated carbon (11.2 g) supporting 10% palladium, and thoroughly degassed N,N-dimethylformamide (500 g) were added to a 1 L four-neck flask, hydrogen gas was filled into the system, and the mixture was stirred strongly at room temperature for 48 hours. After the reaction was completed, the palladium carbon was removed, and the N,N-dimethylformamide was concentrated under reduced pressure. The precipitated solid was dissolved in a minimum amount of DMF and recrystallized using hexane as a poor solvent. The obtained solid was dispersed in methanol and heated and stirred at 80°C for 6 hours. The solid was then collected by filtration and dried under reduced pressure to obtain the desired white solid (35.0 g: 79.5 mmol, yield: 71%). The structure was confirmed by nuclear magnetic resonance spectroscopy [ 1 H-NMR (400 MHz) was performed to confirm that it was the desired compound. The measurement data are shown below.
[0166] 1 H-NMR (400MHz:D6-DMSO)δ:8.36-8.34(dd:2H), 7.56-7.53(q:4H), 6.55-6. 52(q:4H), 5.65(br:4H), 5.14-5.08(q:2H), 3.76-3.72(q:2H), 3.49(s:6H)
[0167] [Synthesis Example 1] 5.06g (11.5mmol) of DA-1 was placed in a 50mL four-neck flask equipped with a stirrer and a nitrogen inlet tube, and 20.3g of NMP was added. The mixture was heated and stirred at 70℃ for 30 minutes while supplying nitrogen to dissolve. This diamine solution was cooled to room temperature with water, and then 2.37g (11.3mmol) of DC-1 was added while stirring, and then 9.50g of NMP was added. The mixture was heated and stirred at 40℃ for 24 hours to obtain a polyamic acid solution (PAA-1). The viscosity of this polyamic acid solution at 25℃ was 300mPa s. The molecular weight and molecular weight distribution of this polyamic acid were Mn = 1.27×10 4 , Mw=3.07×10 4 , Mw / Mn=2.41.
[0168] [Synthesis Examples 2, 3, 4, 5, 6] The diamine components, tetracarboxylic acid components, and NMP shown in Table 1 below were used, and the reaction temperature, solid content, and procedure were carried out in the same manner as in Synthesis Example 1 to obtain polyamic acid solutions PAA-2, PAA-3, PAA-4, PAA-5, and PAA-6 shown in Table 1 below. The viscosities and molecular weights of the obtained polyamic acids are shown in Table 2 below.
[0169] [Table 1]
[0170] [Table 2]
[0171] [Synthesis Example 7] 55.0 g of the obtained polyamic acid solution (PAA-1) was taken in a 100 ml four-neck flask equipped with a stirrer and a nitrogen inlet tube, 18.3 g of NMP was added, and the mixture was stirred at room temperature for 30 minutes. 5.12 g (50.7 mmol) of acetic anhydride and 1.59 g (20.1 mmol) of pyridine were added to the obtained polyamic acid solution, and the mixture was heated and stirred at 55 ° C for 6 hours to perform chemical imidization. The obtained reaction solution was poured into 218 ml of methanol while stirring, and the precipitate was collected, and then washed three times with 218 ml of methanol. The obtained resin powder was dried at 60 ° C for 12 hours to obtain a polyimide resin powder (PIP-1). The imidization rate of this polyimide resin powder was 95% or more.
[0172] [Synthesis Example 8] Chemical imidization was carried out using a polyamic acid solution (PAA-2) with the same amounts of acetic anhydride and pyridine introduced and the same reaction temperature as in Synthesis Example 7. However, a gel-like solid precipitated during heating and stirring, and accurate chemical imidization was not possible.
[0173] [Synthesis Example 9] 24.0 g of the obtained polyamic acid solution (PAA-3) was taken in a 50 ml four-neck flask equipped with a stirrer and a nitrogen inlet tube, 8.00 g of NMP was added, and the mixture was stirred at room temperature for 30 minutes. 2.56 g (25.0 mmol) of acetic anhydride and 1.19 g (15.1 mmol) of pyridine were added to the obtained polyamic acid solution, and the mixture was heated and stirred at 55 ° C for 4 hours to perform chemical imidization. The obtained reaction solution was poured into 107 ml of methanol while stirring, and the precipitate was collected, and then washed three times with 107 ml of methanol. The obtained resin powder was dried at 60 ° C for 12 hours to obtain a polyimide resin powder (PIP-3). The imidization rate of this polyimide resin powder was 95% or more.
[0174] [Synthesis Example 10] 18.0 g of the obtained polyamic acid solution (PAA-3) was taken in a 50 ml four-neck flask equipped with a stirrer and a nitrogen inlet tube, 6.00 g of NMP was added, and the mixture was stirred at room temperature for 30 minutes. 0.77 g (7.53 mmol) of acetic anhydride and 0.30 g (3.80 mmol) of pyridine were added to the obtained polyamic acid solution, and the mixture was heated and stirred at 55 ° C for 2 hours to perform chemical imidization. The obtained reaction solution was poured into 75.2 ml of methanol while stirring, and the precipitate was collected, followed by washing three times with 75.2 ml of methanol. The obtained resin powder was dried at 60 ° C for 12 hours to obtain a polyimide resin powder (PIP-4). The imidization rate of this polyimide resin powder was 73%.
[0175] [Synthesis Example 11] 44.0 g of the obtained polyamic acid solution (PAA-4) was taken in a 50 ml four-neck flask equipped with a stirrer and a nitrogen inlet tube, 14.7 g of NMP was added, and the mixture was stirred at room temperature for 30 minutes. 4.50 g (44.1 mmol) of acetic anhydride and 2.09 g (26.5 mmol) of pyridine were added to the obtained polyamic acid solution, and the mixture was heated and stirred at 55 ° C for 2 hours to perform chemical imidization. The obtained reaction solution was poured into 196 ml of methanol while stirring, and the precipitate was collected, and then washed three times with 196 ml of methanol. The obtained resin powder was dried at 60 ° C for 12 hours to obtain a polyimide resin powder (PIP-5). The imidization rate of this polyimide resin powder was 95% or more.
[0176] [Synthesis Example 12] 96.5 g of the obtained polyamic acid solution (PAA-5) was taken in a 100 ml four-neck flask equipped with a stirrer and a nitrogen inlet tube, 32.2 g of NMP was added, and the mixture was stirred at room temperature for 30 minutes. 7.03 g (68.9 mmol) of acetic anhydride and 3.64 g (46.0 mmol) of pyridine were added to the obtained polyamic acid solution, and the mixture was heated and stirred at 55 ° C for 2 hours to perform chemical imidization. The obtained reaction solution was poured into 433 ml of methanol while stirring, and the precipitate was collected, and then washed three times with 433 ml of methanol. The obtained resin powder was dried at 60 ° C for 12 hours to obtain a polyimide resin powder (PIP-6). The imidization rate of this polyimide resin powder was 62%.
[0177] [Synthesis Example 13] Polyimide resin powder (PIP-7) was obtained by chemical imidization using the polyamic acid solution (PAA-6) in the same manner as in Synthesis Example 12, with the same amounts of acetic anhydride and pyridine introduced and the same reaction temperature. The imidization rate of this polyimide resin powder was 68%.
[0178] The imidization rates of the polyimide resin powders obtained in Synthesis Examples 7, 8, 9, 10, 11, 12 and 13 are shown in Table 3 below.
[0179] [Table 3]
[0180] [Synthesis Example 14] 5.56 g of polyimide resin powder (PIP-1) was placed in a 50 ml eggplant flask, 40.7 g of NMP was added so that the solid concentration was 12%, and the mixture was stirred at 70°C for 24 hours to dissolve the polyimide, obtaining a polyimide solution (PIS-1). No abnormalities such as turbidity or precipitation were observed in this liquid crystal alignment agent, and it was confirmed to be a homogeneous solution. The molecular weight and molecular weight distribution of this polyimide solution were Mn = 1.30 × 10 4 , Mw=3.35×10 4 , Mw / Mn=2.56.
[0181] [Synthesis Example 15] A polyimide solution (PIS-2) was obtained using a polyimide resin solid (PIP-2) in the same manner as in Synthesis Example 14. However, unnecessary substances were generated, and a homogeneous polyimide solution could not be obtained.
[0182] [Synthesis Examples 16, 17, 18, 19, 20] Polyimide resin powders (PIP-3, PIP-4, PIP-5, PIP-6, PIP-7) were used to obtain polyimide solutions (PIS-3, PIS-4, PIS-5, PIS-6, PIS-7) in the same manner as in Synthesis Example 14. The molecular weights of the obtained polyimide solutions are shown in Table 4 below.
[0183] [Table 4]
[0184] When polyamic acid solutions obtained by sequential polymerization of DA-1 or DA-2 and DC-1 were chemically imidized, the polyamic acid made from DA-1 successfully underwent chemical ring closure, whereas the polyamic acid made from DA-2 precipitated a gel-like solid during the chemical ring closure and could not be evaluated.
[0185] By using the DA-1 analogues included in this claim, the solubility in solvents is specifically improved when polyamic acid and its chemically ring-closed polyimide are used compared to the DA-2 analogues. In addition, the materials PIS-1, PIS-3, PIS-4, and PIS-5 included in this claim exhibit properties that can withstand practical use as liquid crystal alignment films, and can further reduce the risk of display defects, as described below.
[0186] [Synthesis Example 21] In a 20 ml sample tube containing a stirrer, 6.50 g of the polyimide solution (PIS-1) obtained in Synthesis Example 1 was taken, 1.00 g of NMP, 3.53 g of GBL solution, and 3.00 g of BCS were added, and the mixture was stirred with a magnetic stirrer for 2 hours to obtain a liquid crystal alignment agent (A-1). Using this liquid crystal alignment agent (A-1), a liquid crystal cell for liquid crystal alignment evaluation and bright spot evaluation was prepared according to the procedure shown below.
[0187] [Synthesis Example 22] Using polyimide solutions (PIS-3, PIS-4, PIS-5, PIS-6, PIS-7), liquid crystal alignment agents (A-2, A-3, A-4, A-5, A-6, A-7) were obtained in the same manner as in Synthesis Example 21.
[0188] Using these liquid crystal alignment agents (A-2, A-3, A-4, A-5, A-6, and A-7), liquid crystal cells for evaluating liquid crystal alignment and bright spots were prepared according to the procedures described below.
[0189] [Example 1] The liquid crystal alignment agent (A-1) obtained in Synthesis Example 21 was filtered through a 1.0 μm filter, and then the liquid crystal alignment agent was spin-coated on a 30 mm × 40 mm ITO substrate and dried on a hot plate at 80 ° C. for 2 minutes. The coated film surface was then exposed to linearly polarized ultraviolet light with an extinction ratio of 26:1 and a wavelength of 254 nm at 0.15 J / cm through a polarizer. 2 from 0.40 J / cm 2 After irradiating with various exposure doses between 100 and 200°C, the substrate was baked in a hot air circulation oven at 230°C for 17 minutes to obtain a substrate with a liquid crystal alignment film. The two obtained substrates were combined into a set, a sealant was printed on the substrate, and another substrate was attached so that the liquid crystal alignment film faces each other and the alignment direction is 0°, and then the sealant was cured to produce an empty cell. Liquid crystal MLC-3019 (Merck) was injected into this empty cell by a reduced pressure injection method, and the injection port was sealed to obtain a liquid crystal cell with liquid crystal alignment. The afterimage evaluation results for each are shown in Table 5 below. The liquid crystal alignment was evaluated based on the above-mentioned evaluation criteria.
[0190] [Examples 2, 3, and 4] Instead of the liquid crystal alignment agent (A-1), each liquid crystal alignment agent (A-2, A-3, A-4) was used, and the UV irradiation amount and baking temperature were the same as in Example 1 to prepare liquid crystal cells for image retention evaluation. The image retention evaluation results for each are shown in Table 5 below.
[0191] [Comparative Examples 1 and 2] Instead of the liquid crystal alignment agent (A-1), the liquid crystal alignment agents (A-5, A-6) were used, and the UV irradiation dose and baking temperature were the same as in Example 1 to prepare liquid crystal cells for image retention evaluation. The image retention evaluation results for each are shown in Table 5 below.
[0192] [Table 5]
[0193] The liquid crystal alignment agent (A-1, A-2, A-3, A-4) consisting of DA-1 and DC-1 described in this claim has an exposure dose of 0.10 J / cm 2 from 0.40 J / cm 2 In addition, copolymerized polyimides using DA-1, other diamine components, and DC-1 also show good image retention properties, and the quality of the image retention properties and the exposure dose vary depending on the diamine components used. For example, in the liquid crystal alignment agent (A-2) obtained by copolymerizing DA-1 and DA-3, the exposure dose is 0.10 J / cm 2 from 0.40 J / cm 2 Furthermore, the liquid crystal alignment agent (A-3) prepared using a polyimide solution (PIS-3) in which the imidization rate was controlled in the process of chemically imidizing polyamides consisting of DA-1 and DA-3, showed better afterimage properties over a wider range of exposure doses. 2 Since it shows good afterimage characteristics before and after, it is a material that can obtain good afterimage characteristics at a very low exposure. Furthermore, like the above-mentioned liquid crystal alignment agent (A-3), the liquid crystal alignment agent (A-4) consisting of DA-1 and DA-4 can also obtain very good afterimage characteristics at a very low exposure.
[0194] On the other hand, the liquid crystal alignment agent (A-5) consisting of DA-3 and DA-5 and DC-1 and DC-2 shown in Comparative Example 1 exhibits good afterimage characteristics, but has a low optical output of 0.20 J / cm 2 In terms of the required exposure amount, the above liquid crystal alignment agents (A-2, A-3, and A-4) require an exposure amount of 0.10 J / cm2 when they exhibit good afterimage characteristics. 2 This suggests the superiority of DA-1, which is included in the present claim. Furthermore, since the required amount of exposure can be adjusted by combining polymer units, it is possible to realize the takt time desired by the user when considering the actual manufacturing site.
[0195] In addition, the liquid crystal alignment agent (A-6) obtained from DA-3, DA-5 and DC-1 has a similar backbone to the above liquid crystal alignment agents (A-1, A-2, A-3, A-4), but does not have good image retention characteristics, suggesting the advantage of using DA-1 included in this claim.
[0196] [Example 5] The liquid crystal cell for evaluating the afterimage, which was prepared using the liquid crystal alignment agent (A-1) in Example 1, was heated in a heating oven at 60°C for more than two weeks, and then observed with a polarizing microscope (ECLIPSE E600WPOL) (manufactured by Nikon Corporation). As described above, the criteria for evaluation were based on the number of bright spots confirmed by polarizing microscope observation, with less than five bright spots being rated as "good" and more than five being rated as "bad." Table 6 shows the bright spot evaluation results of this liquid crystal cell after long-term AC driving in each case.
[0197] [Examples 6, 7, and 8] Instead of the liquid crystal alignment agent (A-1), each liquid crystal alignment agent (A-2, A-3, A-4) was used, and the ultraviolet ray irradiation amount and baking temperature were the same as in Example 5 to prepare liquid crystal cells for evaluating display defects. The display defect evaluation results for each are shown in Table 6 below.
[0198] [Comparative Examples 3 and 4] Instead of the liquid crystal alignment agent (A-1), each liquid crystal alignment agent (A-5, A-6) was used, and the ultraviolet ray irradiation amount and baking temperature were the same as those in Example 5 to prepare liquid crystal cells for evaluating display defects. The display defect evaluation results for each are shown in Table 6 below.
[0199] [Table 6]
[0200] The liquid crystal alignment agents (A-1, A-2, A-3, A-4) made of DA-1 and DC-1 described in this claim show very good results in the evaluation of poor evaluation. On the other hand, the liquid crystal alignment agents made of soluble polyimides obtained by copolymerizing DA-3 and DA-5 and DC-1 and DC-2 shown in Comparative Example 1 and the liquid crystal alignment agents made of soluble polyimides obtained by copolymerizing DA-3, DA-5, and DC-1 showed poor results. The liquid crystal alignment agent made of soluble polyimide using DA-1 included in this claim is also effective in suppressing display defects.
[0201] [Synthesis Example 23] DC-3 / DA-6 Polymerization of Polyamic Acid 4.00g (8.50mmol) of DA-6 was placed in a 50mL four-neck flask equipped with a stirrer and a nitrogen inlet tube, and 40.58g of NMP was added. The mixture was stirred at room temperature for 10 minutes while supplying nitrogen to dissolve the mixture. 1.54g (7.64mmol) of DC-3 was added to this diamine solution while stirring, and the mixture was stirred at room temperature for 24 hours to obtain a polyamic acid solution (PAA-8) with a concentration of 12% by mass. The viscosity of this polyamic acid solution at 25°C was 420mPa s. The molecular weight and molecular weight distribution of this polyamic acid were Mn = 9.82×10 3 , Mw=2.16×10 4 , Mw / Mn=2.20.
[0202] [Synthesis Examples 24, 25, 26, 27, 28, 29] The diamine components, tetracarboxylic acid components, and NMP shown in Table 7 below were used, and the reaction temperature, solid content, and procedure were carried out in the same manner as in Synthesis Example 1 to obtain polyamic acid solutions PAA-9, PAA-10, PAA-11, PAA-12, PAA-13, and PAA-14 shown in Table 7 below. The viscosities and molecular weights of the obtained polyamic acids are shown in Table 8 below.
[0203] [Table 7]
[0204] [Table 8]
[0205] [Synthesis Example 30] 30.0 g of each of the obtained polyamic acid solutions (PAA-8, PAA-9, PAA-10, PAA-11, PAA-12, PAA-13, PAA-14) was taken in a 100 ml four-neck flask equipped with a stirrer and a nitrogen inlet tube, 30.0 g of NMP was added, and the mixture was stirred at room temperature for 30 minutes. 5 mol of acetic anhydride and 5 mol of pyridine were added to the obtained polyamic acid solution relative to the carboxylic acid of the polyamic acid, and the mixture was heated and stirred at 70 ° C for 3 hours to perform chemical imidization. The obtained reaction solution was poured into 500 ml of methanol while stirring, and the precipitate was collected, followed by washing three times with 300 ml of methanol. The obtained resin powder was dried at 80 ° C for 12 hours to obtain polyimide resin powders (PIP-8, PIP-9, PIP-10, PIP-11, PIP-12, PIP-13). As for PIP-14, it gelled during chemical imidization, and therefore it was not possible to obtain it as a polyimide. The molecular weight and imidization rate of this polyimide resin powder are shown in Table 9 below.
[0206] [Table 9]
[0207] [Examples 7 to 12] In a 50 ml eggplant flask, 10.0 g of the polyamic acid solution (PAA-8 to PAA-14) obtained above was weighed out, 4.00 g of NMP and 6.0 g of BCS were added, and the mixture was stirred at room temperature for 24 hours to obtain liquid crystal alignment agents (A-8 to A-14). A-14 was used as a comparison.
[0208] [Examples 13 to 18] 2.0 g of the polyimide resin powder (PIP-8 to PIP-13) obtained above was weighed out into a 50 ml recovery flask, 18.0 g of NMP was added, and the mixture was stirred at room temperature for 24 hours. Further, 6.67 g of NMP and 6.67 g of BCS were added, and the mixture was stirred for 1 hour to obtain liquid crystal alignment agents (A-15 to A-20).
[0209] [Test Example 1] The alignment agents A-8 to A-20 obtained in Examples 7 to 18 were evaluated for the liquid crystal alignment film based on the following method. As comparisons, A-14 (Comparative Example 3) and SE-6414 (Comparative Example 4) manufactured by Nissan Chemical Industries, Ltd. were used.
[0210] <Evaluation of liquid crystal alignment, voltage holding ratio, and pretilt angle> The liquid crystal alignment, voltage holding ratio and pretilt angle were evaluated as follows.
[0211] [Preparation of liquid crystal cells for observing liquid crystal alignment and measuring voltage holding ratio and pretilt angle] After filtering the liquid crystal alignment agent with a 1.0 μm filter, it was applied by spin coating to a substrate with electrodes (a glass substrate with a size of 30 mm wide x 40 mm long and a thickness of 0.7 mm. The electrode was a rectangular ITO electrode with a width of 10 mm and a length of 40 mm and a thickness of 35 nm). After drying for 1 minute on a hot plate at 80 ° C, a substrate was baked for 20 minutes at 120 ° C using an IR oven, and a substrate was baked at 230 ° C. The film thickness was adjusted to 100 nm after baking. This liquid crystal alignment film was rubbed with a rayon cloth (YA-20R manufactured by Yoshikawa Kako) (roller diameter: 120 mm, roller rotation speed: 1000 rpm, moving speed: 20 mm / sec, indentation length: 0.4 mm), and then it was washed by ultrasonic irradiation in pure water for 1 minute, water droplets were removed by air blowing, and then it was dried at 80 ° C for 15 minutes to obtain a substrate with a liquid crystal alignment film.
[0212] Two substrates with the above liquid crystal alignment film were prepared, and 4 μm spacers were sprayed on the liquid crystal alignment film surface of one of them, and then a sealant was printed on top of it. The other substrate was attached so that the rubbing direction was in the opposite direction and the film surface faced each other, and then the sealant was cured to prepare an empty cell. MLC-3019 (manufactured by Merck Ltd.) was injected into this empty cell by the reduced pressure injection method, and the injection port was sealed to obtain a liquid crystal cell. After that, the alignment of the liquid crystal was observed, and then the liquid crystal cell was heated at 110°C for 1 hour and left at 23°C overnight to obtain a liquid crystal cell for measuring the voltage holding ratio.
[0213] Using the liquid crystal cell for measuring the voltage holding ratio obtained by the above procedure, a voltage of 1V was applied for 60μs at a temperature of 60℃, the voltage was measured after 166.7ms, and the voltage holding ratio was calculated as the extent to which the voltage was held. The voltage holding ratio was measured using a VHR-1 voltage holding ratio measuring device manufactured by Toyo Corporation.
[0214] [Evaluation of pretilt angle] The pretilt angle was measured using an Axo Scan Mueller matrix polarimeter manufactured by Optometrics.
[0215] [Evaluation of rubbing resistance] After filtering the liquid crystal alignment agent with a 1.0 μm filter, it was applied by spin coating to a substrate with electrodes (a glass substrate with a size of 30 mm wide x 40 mm long and a thickness of 1.1 mm. The electrode was a rectangle with a width of 10 mm and a length of 40 mm, and an ITO electrode with a thickness of 35 nm). After drying for 1 minute on a hot plate at 80 ° C, a substrate was baked for 20 minutes at 120 ° C using an IR oven, and a substrate was baked at 230 ° C. The film thickness was adjusted to 100 nm after baking. This liquid crystal alignment film was rubbed with a rayon cloth (YA-20R made by Yoshikawa Kako) (roller diameter: 120 mm, roller rotation speed: 1000 rpm, moving speed: 20 mm / sec, indentation length: 0.5 mm), and then the rubbing resistance was evaluated using a confocal laser microscope. If peeling occurred, it was judged as peeling, if many scrapes or scratches were observed, it was judged as poor, and if good, it was judged as good.
[0216] [Evaluation of liquid crystal alignment] The liquid crystal alignment property was evaluated based on the same evaluation criteria as in Example 1. In addition, "◯" in the evaluation criteria was defined as "good", and "×" in the evaluation criteria was defined as "bad". The results of the above-mentioned various evaluations are shown in Tables 10 to 13.
[0217] <Evaluation results of alignment agent printability, rubbing resistance, and cell display characteristics>
[0218] [Table 10]
[0219] [Table 11]
[0220] [Table 12]
[0221] [Table 13]
[0222] When a film is formed by baking at 120°C, polyamic acid in particular cannot be imidized under these conditions, so the physical strength becomes very weak, and the film is scraped off by rubbing treatment, which tends to deteriorate the alignment of liquid crystals. However, the polyamic acid and polyimide using the diamine of the present invention have excellent rubbing resistance even when baked at a low temperature, and the alignment of liquid crystals is also good. Furthermore, they are characterized by a very small pretilt angle and high VHR.
[0223] Furthermore, the diamine of the present invention can be made very soluble. PAA-14, which does not contain diamine, could not be chemically imidized, but PIP-13, which contains 50 mol% of diamine, can be adjusted to an imidization rate of 95% or more without any problems, and good alignment film properties are obtained. In general, when a component with very poor solubility such as DC-1 or DC-4 is incorporated, chemical imidization is often difficult, but by using the diamine of the present invention, it becomes possible to adjust a soluble polyimide with a high imidization rate. By making it a soluble polyimide, reliability can be further improved.
[0224] In the case of baking at 230°C, the material of the comparative example also undergoes imidization, improving the rubbing resistance, liquid crystal alignment, and reliability, but the alignment agent of the present invention shows good characteristics and tends to slightly improve the pretilt angle, but this is a very small advantage compared to the comparative example. Furthermore, the reliability is also very high.
[0225] Therefore, by using the diamine of the present invention, a liquid crystal aligning agent that can be baked at low to high temperatures can be produced, and further an alignment film with a very low pretilt can be obtained.
[0226] [Test Example 2] The liquid crystal alignment agents (A-16, A-17, A-20) obtained in Examples 14, 15, and 18, and the liquid crystal alignment agent A-5 of the comparative example were filtered through a 1.0 μm filter, and then the liquid crystal alignment agent was spin-coated on a 30 mm × 40 mm ITO substrate, dried on a hot plate at 80 ° C. for 2 minutes, and irradiated the coated surface with linearly polarized ultraviolet light having a wavelength of 254 nm and an extinction ratio of 26:1 through a polarizer at 0.1 to 1.0 J / cm. 2 After irradiating the substrates in the range of 100° C., they were baked in a hot air circulating oven at 150° C. for 20 minutes to obtain a substrate with a liquid crystal alignment film. The two obtained substrates were combined into a set, a sealant was printed on the substrate, and another substrate was attached to the set so that the liquid crystal alignment film faces each other and the alignment direction is 0°. The sealant was then cured to produce an empty cell. Liquid crystal MLC-3019 (Merck) was injected into the empty cell by a reduced pressure injection method, and the injection port was sealed to obtain a liquid crystal cell with liquid crystal alignment. The results of the liquid crystal alignment in each case are shown in Table 14 below. The evaluation was performed based on the same evaluation criteria as in Example 1.
[0227] [Table 14]
[0228] It was found that the soluble polyimide using the diamine of the present invention and DC-1 exhibited orientation when pre-dried, irradiated with UV light, and baked at 150°C. The material of Comparative Example 1 exhibited orientation at high temperatures, but did not exhibit orientation at low temperatures, regardless of the UV irradiation intensity. It was therefore found that photo-alignment at low temperatures was possible by using the diamine of the present invention. [Industrial Applicability]
[0229] The polyamic acid and polyimide obtained from the diamine of the present invention have excellent solubility in solvents, making it possible to manufacture liquid crystal alignment agents and films that have not been realized in terms of solubility. In addition, they can be widely used in a wide range of applications, from alignment films for rubbing to photo-alignment films. In particular, they are expected to be able to handle low-temperature baking, low pretilt angle materials, and simplified photo-alignment processes, which will be trends in the in-plane switching system in the future.
[0230] A liquid crystal display element having a liquid crystal alignment film manufactured from the material of the present invention has excellent afterimage characteristics and long-term display stability, and can be suitably used in large-screen, high-definition liquid crystal televisions, small and medium-sized car navigation systems, smartphones, etc. Furthermore, since it can be manufactured more simply in the manufacturing process, it is expected to improve yield and production efficiency.
Claims
1. A diamine represented by the following formula [1]: 【Chemistry 1】 In formula [1], Y 1 is a tetravalent organic group represented by formula [Y 1 -1], X 1 and X 2 are divalent organic groups having a phenylene group, and Z 1 , Z 2 are each independently a single bond, -NH-, or -O-; R 1 and R 2 each independently represents an alkyl group having 1 to 5 carbon atoms. 【Chemistry 2】 (In formula [Y 1 -1], R 5 to R 8 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group, and may be the same or different.)
2. A polymer obtained from a diamine component comprising the diamine according to claim 1.
3. A method for producing a diamine compound, comprising starting from a compound of the following formula (11) and producing the diamine according to claim 1 via a compound of the following formula (12) or a compound of the following formula (13). 【Chemistry 3】 【change】 【change】 In formulas (11) to (13), Y 1 is a tetravalent organic group represented by the formula [Y 1 -1], R 1 and R 2 Each independently represents an alkyl group having 1 to 5 carbon atoms. 31 and R 32 represents a hydrogen atom or an amino-protecting group. 【Chemistry 4】 (In formula [Y 1 -1], R 5 to R 8 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group, and may be the same or different.)
Citation Information
Patent Citations
Liquid crystal aligning agent, liquid crystal alignment film and liquid crystal display element
JP2013080193A
Rheumatic autoimmune disease antigen
WO2000074705A1
Liquid crystal aligning agent
WO2010053128A1